ANALISIS DAYA SAING KOMPETITIF DAN KOMPARATIF PADA INDUSTRI KECIL GULA KELAPA DI DESA PURBOSARI KECAMATAN SELUMA BARAT KABUPATEN SELUMA - Martadiningrum, Utari; Sukiyono, Ketut; Sriyoto, Sriyoto (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
This research aimed at measuring the level of competitive and comparatives advantages of small palm sugar industries in Purbosari village Seluma Regency. This research used secondary and primary data. Respondents in this research censused from 80 palm sugar producers. The data collected from respondents is data weekly traced five successive weeks. Analysis method used cost unit approach to measure advantages level as proposed by Coocburn and Siggel (1998). The research showed that the average of unit cost ratio competitive and comparative advantage small palm sugar industries in the purbosari village is less than 1, that is, 0.65 and 0.42. This indicates that palm sugar in purbosari village has high competitiveness degree. Meanwhile. its NPCO value 0.64 indicating there is no government protection on palm sugar output.